2020
DOI: 10.1080/10810730.2020.1840676
|View full text |Cite
|
Sign up to set email alerts
|

SNS Usage and Third-person Effects in the Risk Perception of Zika Virus among Singaporean Women

Abstract: This study examines the SNS activities of Singaporean women to assess how they perceive the risk of Zika virus infection based on the consumption of Zika-related news. Results from an online survey (N = 510) confirmed that third-person risk perception exists among study participants. Individual posting of ZIKA-related news on SNSs was negatively associated with third-person perception. Additionally, third-person perception was negatively correlated with preventive behavioral intention. A moderated mediation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, previous studies have shown that there are scenarios where the public ignores the epidemic information. According to Davison’s third-person hypothesis [ 52 ], people are optimistically biased and would perceive others as being more vulnerable than themselves [ 53 ]. Increased psychological distance may lead individuals to view the risk more abstractly and discount it more heavily than those who perceive the risk as psychologically proximal and concrete [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that there are scenarios where the public ignores the epidemic information. According to Davison’s third-person hypothesis [ 52 ], people are optimistically biased and would perceive others as being more vulnerable than themselves [ 53 ]. Increased psychological distance may lead individuals to view the risk more abstractly and discount it more heavily than those who perceive the risk as psychologically proximal and concrete [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNS dependency was measured by using questions developed in previous studies [ 35 , 42 ]. ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, specific types of SNS use were shown to be related to distinct judgments about risks. For instance, Jung et al [ 35 ] examined the consumption of Zika-related news on social media and how it was related to perception of the risk of Zika virus infection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the implications of the TPEs in medical contexts have been studied before (Jung et al, 2020;Lee and Park, 2016), little is known about how TPE functions on COVID-19 vaccination. We could only identify two studies revealing that people consider close and distant others to be more vulnerable to disinformation (Liu and Huang, 2020) and misinformation (Cheng and Luo, 2020) in the context of the COVID-19 outbreak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This line of reasoning encompassed in the TPE might also be applied to the perceived usefulness of SNSs in general. Moreover, a recent survey conducted on Singaporean women signalled that a behaviour consisting of posting news related to the ZIKA virus on SNS proved to be a predictor of TPE (Jung et al, 2020). Therefore, we assume that:…”
Section: Predictors Of Third-person Perceptionsmentioning
confidence: 99%